2009
DOI: 10.2139/ssrn.1514291
|View full text |Cite
|
Sign up to set email alerts
|

What Explains the Low Profitability of Chinese Banks?

Abstract: BANCO DE ESPAÑA(*) The opinions expressed are those of the authors and not necessarily those of the Banco de España or Banco Bilbao Vizcaya Argentaria. We would like to thank Maitena Duce and Pablo García-Luna for their excellent assistance with some of the data. We also thank José Manuel Montero, Daniel Navia, Jesús Saurina and Francisco Vázquez and three anonymous referees for their comments. All remaining errors are obviously ours.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
196
2
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(210 citation statements)
references
References 29 publications
10
196
2
2
Order By: Relevance
“…Our study contributes to the empirical literature in the following ways: 1) it examines in depth different types of risk; and 2) uses more accurate measures of efficiency (SFA) and competition (Lerner index and 3-bank concentration ratio). It therefore provides more robust results with regard to the impacts of competition and efficiency on bank profitability compared to Garcia-Herrero et al (2009) …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our study contributes to the empirical literature in the following ways: 1) it examines in depth different types of risk; and 2) uses more accurate measures of efficiency (SFA) and competition (Lerner index and 3-bank concentration ratio). It therefore provides more robust results with regard to the impacts of competition and efficiency on bank profitability compared to Garcia-Herrero et al (2009) …”
Section: Discussionmentioning
confidence: 99%
“…Using a sample of Chinese commercial banks over the period 2003-2009, Tan and Floros (2014 investigate the inter-relationship between risk, profitability and competition in the Chinese banking industry. Two types of risk are considered -credit risk and insolvency risk -while competitive conditions are measured by the Lerner index.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, several studies around that time focused on estimating the effect of corporate governance on asset quality (Grove et al 2011;Liang et al 2013;O'Sullivan et al 2016). In keeping with extant literature (García-Herrero et al 2009;Liang et al 2013), we use (i) net non-performing assets to total loans and advances (Nnpa_ttladv); (ii) gross non-performing assets to total loans and advances (Gnpa_ttladv); (iii) addition of net non-performing assets to total loans and advances (Nnpa_additn_ttladv) and (iv) addition of gross non-performing assets to total loans and advances (Gnpa_additn_ttladv) as our measures of asset quality. While the first two of these measures capture the quality of the stock of bank assets and proxy for bank's cumulative lending behaviour, the next two are essentially flow measures that capture the quality of its current lending practices.…”
Section: Dependent Variable: Bank Outcomesmentioning
confidence: 99%
“…The performance of FCC banks was below world standard. The annual reports of the Association of Banks in FCC, namely: Palestine, Jordan, and Lebanon showed that the average return on assets (ROA) for FCC banks is 0.66, where the world standard of ROA is 1.8% according to (García-Herrero et al, 2009). Moreover, the world bank reports (The World Bank, Available at: https://research.stlouisfed.org/fred2/search?st=RO A+in+GCC+counries) during the last five years [2010][2011][2012][2013][2014] showed that the average ROA to GDP ratio in FCC region is 0.23 and the average ROE to GDP is 2.13 percent as shown in Table 1.…”
Section: Introductionmentioning
confidence: 99%